FABRICATION AND CHARACTERIZATION OF SOFT COMPOSITE MAGNET BaFe12O19 - SiO2 - ginting, masno; Sebayang, Perdamean; N, Nasrudin M (Teknologi Indonesia, 2015)
Preparation and characterization of soft magnetic BaFe12O19?SiO2 has been successfully carried out by mixing BaFe12O19 powder with SiO2 powder. The ratios of Ba Fe12O19/SiO2 used were 100:0, 80:20, 70:30, 60:40, and 50:50 by percent weight. Mixing process was carried out with a dry milling method using planetary ball mill (PBM) for 48 hours. The mixed powder then was pressed at 35 kgf/cm2 on anisotrophy condition to produce pellets with a diameter of 12 mm and 3?5 mm thicknesses. The pellets then were sintered at temperatures of 600, 650, 700, 750, and 800C, each of which was held for 2 hours. The XRD measurement showed that there were three phases appearing, i.e. BaFe12O19 as the majority, and SiO2 and Fe3O4 as minorities. Meanwhile, the result from SEM measurement showed that the grain size was less than 1 ?m. The best magnetic properties were obtained for the composition of 80 wt% BaFe12O19 and 20 wt% SiO2 with sintering temperature at 800C, where the coercivity value (Hc), remanence (Br) and maximum energy product (BHmax) were 1.656 kOe, 0.81 kG, and 0.414 MGOe, respectively.